Treatment and outcome of patients after cardiopulmonary resuscitation admitted to the intensive cardiac care unit - Pechman, Vratislav; Rokyta, Richard; Gajdoš, Petr; Pešek, Jan (Neuro-endocrinology letters, 2009)
OBJECTIVES: Sudden circulatory arrest is most often of cardiac origin. Our aim was to evaluate circulatory arrest etiology and treatment strategies in patients after cardiopulmonary resuscitation (CPR) with persistent impairment of consciousness in relation to survival and the subsequent quality of life. DESIGN: Retrospective analysis of patients after CPR treated according to the local protocol including mild hypothermia in the intensive cardiac care unit. RESULTS: Over 2 years, we admitted 57 mechanically ventilated patients after CPR. 47 patients (82%) were resuscitated outside the hospital. In 33 patients (58%) the initial rhythm was ventricular fibrillation; in the remaining patients (42%) asystole/pulseless electrical activity. Urgent coronary angiography was performed in 36 patients and percutaneous coronary intervention in 25 of them. The admission APACHE II score was 32,4 +/- 3,4 with predicted mortality of 77,1%. The hospital survival rate was 54% and 47% of the patients were discharged home in a good state of health (Glasgow outcome score 4-5). CONCLUSION: Our results suggest that comprehensive post-resuscitation care including therapeutic hypothermia and percutaneous coronary intervention in selected cases may have a positive impact on the prognosis of patients after CPR.
Keywords: výsledek terapie; kardiopulmonální resuscitace; jednotky intenzivní péče; Intensive Care Units; Male; kvalita života; retrospektivní studie; Hypothermia, Induced; Quality of Life; Survival Rate; Critical Care; srdeční zástava; Aged; mužské pohlaví; senioři; Heart Arrest; Treatment Outcome; terapeutická hypotermie; lidé; Cardiopulmonary Resuscitation; ženské pohlaví; Humans; péče o pacienty v kritickém stavu; Retrospective Studies; Female; lidé středního věku; míra přežití; Middle Aged